Vanadium compounds therapeutic effects in melanoma. (3rd August 2021) - Amante, Cristina I; Aureliano, Manuel; De Sousa-Coelho, Ana Luísa
Abstract: Background: Polyoxometalates are a diverse family of metal-oxo anions of early transitional metal ions in high oxidation states, including vanadium. Such compounds are gaining increasing interest in biomedicine due to their anti-cancer activity. Regarding melanoma, available therapies' effectiveness is still currently limited, commonly leading to relapse. For this reason, it is vital to identify novel anti-cancer agents. Methods: To better understand the mechanism of action involved in the anti-cancer vanadium-based compounds in melanoma, we conducted a systematic review. Search was performed in Clinical Trials, Cochrane Library, Pubmed, Scielo, and Web of Science (20/4-8/5/2020). Review articles were excluded. Inclusion criteria considered articles between 2000 and 2020, written in English, in which vanadium compounds were evaluated alone (not combined with other drugs), allowing to recognise the effects exclusively derived from vanadium. Results: Based on the inclusion/exclusion criteria, a total of 5 articles, published between 2013 and 2020, were analyzed. All tested compounds, including Oxidovanadium(IV) complexes [V IV O(mpp)2 ] and [V IV O(ppp)2 ] (VS3, VS4), reduced cellular viability. Moreover, Vanadium pentoxide (V2 O5 ) and Xyloglucan from Copaifera Langsdorffii complexed with Oxovanadium(IV/V) (XGC:VO), in murine B16F10 cells, and Inorganic anion vanadate (VN), [V IV O (dhp)2 ] (VS2), and N, N'-ethylenebis (pyridoxylideneiminato) vanadium(IV) complex [Pyr2 enV(IV)], in A375 cells, induced apoptosis. VN, VS2 and Pyr2 enV(IV) increased reactive oxygen species (ROS) levels in A375 cells. In vivo experiments demonstrated that V2 O5 prolonged the life of mice implanted with B16F10 cells, with no systemic toxicity. Conclusions: Several different vanadium-based compounds have anti-cancer potential in melanoma, mainly increasing apoptosis and ROS production. Specific metal-based complexes are potential melanoma treatments, which might have been previously neglected.